1993
DOI: 10.1007/bf00788876
|View full text |Cite
|
Sign up to set email alerts
|

Improved functional recovery after ischemic preconditioning in the globally ischemic rabbit heart is not mediated by adenosine A1 receptor activation

Abstract: Experiments were carried out to test the hypothesis that preconditioning reduces the impairment of recovery of cardiac mechanical function and that this effect is mediated by activation of adenosine A1 receptors. Isolated hearts were Langendorff-perfused at 37 degrees C with oxygenated blood and paced at 3 Hz. They were divided into 5 groups, all subjected to 45 min global ischemia followed by one hour of reperfusion: 1) Control hearts (n = 7) which received no treatment or short ischemia before the long ische… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

1996
1996
2009
2009

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…In these investigations, we have used SPT, DPCPX, GR-69019X, and MRS-1191/MRS-1220 at previously reported concentrations that putatively allow for the selective antagonism of adenosine A 1 and/or A 3 receptors (1,7,8,15,24). Previous reports (1,9,10,15) have indicated that SPT is a nonselective antagonist (A 1 /A 2 /A 3 ) that blocks all adenosine receptor subtypes in the rabbit heart, whereas DPCPX is selective for A 1 receptors in the rabbit myocardium. Hill et al (10) reported that the inhibitory constants (K i values) for the inhibition of 125 I-labeled N 6 -(4-amino-3-benzyl)adenosine (ABA) to rabbit A 1 receptors are 430 Ϯ 279 for SPT compared with 1 Ϯ 0.1 for DPCPX compared with K i values of 37,797 Ϯ 4,409 for SPT and 1,120 Ϯ 145 for DPCPX for the inhibition of 125 Ilabeled ABA to rabbit A 3 receptors.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In these investigations, we have used SPT, DPCPX, GR-69019X, and MRS-1191/MRS-1220 at previously reported concentrations that putatively allow for the selective antagonism of adenosine A 1 and/or A 3 receptors (1,7,8,15,24). Previous reports (1,9,10,15) have indicated that SPT is a nonselective antagonist (A 1 /A 2 /A 3 ) that blocks all adenosine receptor subtypes in the rabbit heart, whereas DPCPX is selective for A 1 receptors in the rabbit myocardium. Hill et al (10) reported that the inhibitory constants (K i values) for the inhibition of 125 I-labeled N 6 -(4-amino-3-benzyl)adenosine (ABA) to rabbit A 1 receptors are 430 Ϯ 279 for SPT compared with 1 Ϯ 0.1 for DPCPX compared with K i values of 37,797 Ϯ 4,409 for SPT and 1,120 Ϯ 145 for DPCPX for the inhibition of 125 Ilabeled ABA to rabbit A 3 receptors.…”
Section: Discussionmentioning
confidence: 99%
“…The concentration of SPT (A 1 /A 2 /A 3 ) used in these experiments was derived from the previous investigation of Hen-drikx et al (9). The concentration of DPCPX (A 1 ) used in these experiments was derived from previous investigation by others (1,14).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To more directly test for a role of AR activation in triggering nonpharmacological forms of PC, AR antagonists or adenosine deaminase have been added, often in both trigger and mediation phases, to limit any contributions from ARs. A number of these studies independently provided no evidence for essential roles for ARs in PC (Liu and Downey 1992; Lasley et al 1993; Hendrikx et al 1993; Bugge and Ytrehus 1995; Lasley et al 1995b), leading to premature elimination of this class of GPCRs as contributing to PC (Cave et al 1993; Li and Kloner 1993). In the context of protective thresholds and contributions of multiple stimuli, a more accurate conclusion may be that the roles of ARs in triggering/mediating PC are redundant, with other concomitant stimuli (e.g., endogenous opioids and bradykinin) being able to compensate and surpass the signaling threshold required for protection.…”
Section: Cardioprotection Via Preischemic Ar Activation: a Role In mentioning
confidence: 99%
“…Since then the protective effects of PC have been described and confirmed in various experimental settings. It was shown that PC markedly reduces the severity of ischaemia and reperfusion-induced ventricular arrhythmias (Shiki and Hearse, 1987;Végh et al 1990Végh et al , 1992a and improves the restoration of contractile dysfunction following reperfusion (Cave and Hearse, 1992;Hendrikx et al, 1993). Somewhat later it was also turned out that not only the brief periods of I/R insults, but other stimuli, such as cardiac pacing (Végh et al, 1991a), heavy physical exercise (Babai et al, 2002), heat stress (Cumming et al, 1996), an increase in myocardial stretch (Ovize et al, 1994), as well as various pharmacological agents can induce a PC-like protection.…”
Section: The Phenomenon Of Ischaemic Preconditioning: From Experimentmentioning
confidence: 99%